The Disclosure of Islamic Values-Annual Report The Analysis of Bank Muamalat Indonesia's Annual Report - Sofyan Syafri Harahap (Jurnal Iqtisad, 2002)
In a capitalist system apt annual report that includes financial statement is assumed to provide sound information concerning a given company. The annual report offers a background to a company, its financial position, operational results, and its performance According to radical economics, a financial statement serves the interests of capitalists (Belkaoui, 1984) Annual reports are also value free and are not concerned with issues such as justice or ethics. Indeed, current trends in accounting have raised some questions concerning the paradigm of traditional accounting theory and especially its bias concerning capitalist interests. The emergence of Employee Reporting Value Added Accounting, Socio Economic Accounting, and Environmental Accounting to name just a few, is evidences of the shortcomings of the capitalistic accounting system in establishing both just and fair principles among company stakeholders This has therefore led to a demand for a new approach towards accounting disclosure including among others things: a clear account of how a company treats its employees, society, the environment and the beliefs of employees. Even though the standard formulated by AAOIFI (1998) based on capitalistic accounting, are still in a theoretical stage of development they can be used as a starting point that may help lead to an improved set of disclosure criteria that can be used by an Islamic bank or organization. This paper will discuss the empirical evidence derived from one such Islamic organization. Bank Muamalat Indonesia, has compiled information using capitalistic accounting standards so as to clarify its financial position and results of operations to stakeholders. It is hypothesized though, that the current disclosures system employed gives no indication of justness or fairness and so is incompatible with Islamic value. The paper argues Muslim researcher should aim to move from utilizing capitalistic practice primarily concerned with the disclosure, of 'financial indicators and towards a system that also consider justice, fairness, and ethical practices.